Facilitating Family Business Diversification Through Extra-Industry Network: Evidence From South Eastern Nigeria - Agbim, Kenneth Chukwujioke (Archives of Business Research, 2018)
Extra-industry network facilitates the identification of opportunities, development of the requisite up-to-date capabilities and acquisition of other complementary resources needed for diversification. However, in spite of these contributions, family businesses in South Eastern Nigeria that are involved in extra-industry network are still staffed with persons, whose capabilities are not regularly improved; to some extent rarely extending their capabilities to other lines of business. Consequent upon these, this study sought to examine the effect of extra-industry network on family business diversification in South Eastern Nigeria. Survey design was adopted for the study. Proportionate stratified random sampling and simple random sampling techniques were employed to select the sample size. Linear regression was used to analyze the collected data through questionnaire. It was found that extra-industry network has significant and positive effect on family business diversification. This study therefore presents extra-industry network to family business founder/CEOs or descendant/CEOs as a strategy for achieving family business diversification. The study recommends collaboration among family firms from diverse industries. This has the advantage of enhancing the diffusion of knowledge/experience on various types of businesses. The trickledown effect of such diffusion is that it can trigger family businesses to use existing or new technologies to start new businesses for the purpose of further satisfying existing or new markets.